A Reaction to the Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care - Ulrich, Lawrence P. (Christian bioethics, 2001)
Lawrence P. Ulrich; A Reaction to the Consensus Statement of the Working Group on Roman Catholic Approaches to Determining Appropriate Critical Care, Christian